2016
DOI: 10.1038/srep26717
|View full text |Cite
|
Sign up to set email alerts
|

Phage selection restores antibiotic sensitivity in MDR Pseudomonas aeruginosa

Abstract: Increasing prevalence and severity of multi-drug-resistant (MDR) bacterial infections has necessitated novel antibacterial strategies. Ideally, new approaches would target bacterial pathogens while exerting selection for reduced pathogenesis when these bacteria inevitably evolve resistance to therapeutic intervention. As an example of such a management strategy, we isolated a lytic bacteriophage, OMKO1, (family Myoviridae) of Pseudomonas aeruginosa that utilizes the outer membrane porin M (OprM) of the multidr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
493
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 529 publications
(556 citation statements)
references
References 49 publications
15
493
3
2
Order By: Relevance
“…This is in contrast with previous studies reporting beneficial effects of phage–antibiotic combinations on Escherichia coli biofilms (Ryan, Alkawareek, Donnelly, & Gilmore, 2012) and planktonic P. aeruginosa cultures (Torres‐Barceló et al., 2016). However, phage–antibiotic effects are not always observed (Verma et al., 2009), which could be due to the specific phage species and class of antibiotic as PAS often requires mechanistic compatibility between the two (Chan et al., 2016; Comeau et al., 2007; Kamal & Dennis, 2015). For example, it has recently been reported that associations between phage and gentamycin resistance are predominantly positive, while associations between phage and ciprofloxacin resistance are mainly negative with natural and clinical E. coli isolates (Allen, Pfrunder‐Cardozo, Meinel, Egli, & Hall, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is in contrast with previous studies reporting beneficial effects of phage–antibiotic combinations on Escherichia coli biofilms (Ryan, Alkawareek, Donnelly, & Gilmore, 2012) and planktonic P. aeruginosa cultures (Torres‐Barceló et al., 2016). However, phage–antibiotic effects are not always observed (Verma et al., 2009), which could be due to the specific phage species and class of antibiotic as PAS often requires mechanistic compatibility between the two (Chan et al., 2016; Comeau et al., 2007; Kamal & Dennis, 2015). For example, it has recently been reported that associations between phage and gentamycin resistance are predominantly positive, while associations between phage and ciprofloxacin resistance are mainly negative with natural and clinical E. coli isolates (Allen, Pfrunder‐Cardozo, Meinel, Egli, & Hall, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Positive correlation between phage selection and antibiotic resistance is in contrast with previous studies showing an opposite effect where phage treatment reduced the emergence of antibiotic resistance (Jalasvuori, Friman, Nieminen, Bamford, & Buckling, 2011; Zhang & Buckling, 2012). One explanation for this discrepancy is that phage–antibiotic synergies could be very specific to the given phage species and type of antibiotics, whereas antibiotic selection‐mediated susceptibility to phages could have been driven by some degree of collateral sensitivity (Chan et al., 2016; Comeau et al., 2007; Kamal & Dennis, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ainsi, en cas d'utilisation large, l'impact écologique de la phagothérapie sur les populations bactériennes devra faire l'objet d'une surveillance adéquate de façon à ne pas reproduire les erreurs du passé observées avec les antibiotiques. Par ailleurs, dans certains cas, l'apparition de la résistance aux phages peut s'accompagner d'une diminution ou d'une perte de la virulence bactérienne [25][26][27], ou d'une re-sensibilisation de la bactérie à des antibiotiques auxquels elle était initialement résistante [28]. Enfin, compte tenu de la grande diversité virale existante, l'acquisition d'une résistance est de moindre portée que pour les antibiotiques : la recherche d'un nouveau phage actif s'avère beaucoup plus aisée et rapide que celle d'une nouvelle molécule antibiotique.…”
Section: Résistanceunclassified